Global positioning system for expressway tolling system - Shatishwaran, Sivalingam (2022)
In Malaysia and any other developing countries, tolling system has a lot of major issues such as traffic congestion that need to be solved. This is where the deployment of the GPS expressway tolling system is able to solve the lingering issues that perceive till this day and by replacing the current tolling system. The main objective of this research is to Encourage the use of e-wallets in tolling systems to make it easier for end users. Furthermore, by avoiding traffic jams at toll booths, able to drive without worrying about toll payment. Moreover, the introduction of the GPS Expressway Tolling system and the background reason why the project is focusing on overcoming the current tolling system. By avoiding traffic congestion at toll booths, able to drive without worrying about paying the toll. This research reflects how the GPS Tolling system differs from other tolling systems and how it is able to overcome many issues which the previous tolling system was unable to resolve. A general overview of our Final Year Project, (GPS Expressway Tolling System) and how it operates and functions, with a focus on how it works and what it can achieve.